Analysis of Tropical Coastal City Development toward the Sustainable Development Goals in Bengkulu City, Indonesia - Akbar Abdurrahman Mahfudz; Ariasari, Ana; Ali Muqsit; Nabiu, Nur Lina Maratana; Suci, An Nisa Nurul (Sustainability (STPP) Theory, Practice and Policy, 2025)
Coastal cities like Bengkulu, in tropical coastal areas, possess natural potential and human resources for sustainable development. Despite this, they face climate change impacts and socio-economic vulnerabilities. This study employs regional analysis techniques to comprehensively understand the multidimensional aspects of developing diverse tropical coastal cities like Bengkulu. The method involves analyzing economic, social, and geographical factors. The research findings reveal a distinct regional typology within Bengkulu Province, with Bengkulu City emerging as an advanced and rapidly growing area. Economic sectors in Bengkulu City, particularly in the coastal region, exhibit advanced and fast-growing characteristics. Ratu Samban Sub-district stands out as a critical growth hub, while Kampung Melayu and Sungai Serut Sub-districts face lower hierarchy levels based on the scalogram index. This concentration of growth aligns with urbanization and economic development theories. The study emphasizes the urgency of inclusive development to ensure every area is included in achieving sustainable and equitable progress, contributing to the broader global agenda of the SDGs